2015
DOI: 10.1515/botcro-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of peanut (Arachis hypogaea L.) cultivars to water deficit stress: status of oxidative stress and antioxidant enzyme activities

Abstract: -From a fi eld experiment, the changes in oxidative stress and antioxidant enzyme activities were studied in six Spanish peanut cultivars subjected to 25−30 days of water defi cit stress at two different stages: pegging and pod development stages. Imposition of water defi cit stress signifi cantly reduced relative water content, membrane stability and total carotenoid content in all the cultivars, whereas total chlorophyll content increased at pegging stage but decreased at pod developmental stage. Chlorophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 39 publications
1
11
0
2
Order By: Relevance
“…This ultimately builds up a better survival capacity in T under higher salinity stress conditions, as also reported by Khare et al (2010) and Rai et al (2013). Likewise, in transgenic MuNAC4 peanut (Pandurangaiah et al 2014) and AtDREB1A peanut (Bhatnagar et al 2009), mtlD tomato (Khare et al 2010) and in some peanut cultivars (Chakraborty et al 2015), enhanced SOD, CAT, and POD activities were reported in response to various abiotic stresses. Besides, even exogenous application of mannitol is also reported to enhance the antioxidative enzymes activity of metal-induced oxidative stress tolerance in wheat (Adrees et al 2015).…”
Section: Relative Water Content (Rwc)supporting
confidence: 74%
“…This ultimately builds up a better survival capacity in T under higher salinity stress conditions, as also reported by Khare et al (2010) and Rai et al (2013). Likewise, in transgenic MuNAC4 peanut (Pandurangaiah et al 2014) and AtDREB1A peanut (Bhatnagar et al 2009), mtlD tomato (Khare et al 2010) and in some peanut cultivars (Chakraborty et al 2015), enhanced SOD, CAT, and POD activities were reported in response to various abiotic stresses. Besides, even exogenous application of mannitol is also reported to enhance the antioxidative enzymes activity of metal-induced oxidative stress tolerance in wheat (Adrees et al 2015).…”
Section: Relative Water Content (Rwc)supporting
confidence: 74%
“…This study demonstrated that water stress led to differential responses in peanut genotypes. The reduction in the number of leaves is presumably a response to the decrease in leaf water content and changes in membrane stability under water stress (Chakraborty et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Nilai RWC daun ≥85% menunjukkan tanaman berada pada kondisi cukup air. Pada kondisi kekeringan, nilai RWC dapat turun hingga 60% atau lebih rendah (Clavel et al, 2004;Rahimi et al, 2010;Vurayai et al, 2011;Shinde dan Laware, 2014;Chakraborty et al, 2015). Penurunan nilai RWC ini berhubungan dengan penurunan penyerapan air oleh akar tanaman pada kondisi tanah yang semakin kering.…”
Section: Kandungan Air Relatif (Relative Water Content Rwc) Daununclassified